The company a short history of a revolutionary idea - Micklethwait, John; Wooldridge, Adrian (Phoenix, an imprint of Orion Books Ltd, 2005)
Economist editors John Micklethwait and Adrian Wooldridge reveal the company to be one of history's great catalysts, for good and for ill, a mighty engine for sucking in, recombining, and pumping out money, goods, people, and culture to every corner of the globe. What other earthly invention has the power to grow to any size, and to live to any age? What else could have given us both the stock market and the British Empire? The company man, the company town, and company time? Disneyfication and McDonald'sization, to say nothing of Coca-colonialism? Through its many mutations, the company has always incited controversy, and governments have always fought to rein it in. Today, though Marx may spin in his grave and anarchists riot in the streets, the company exercises an unparalleled influence on the globe, and understanding what this creature is and where it comes from has never been a more pressing matter.